2020
DOI: 10.1093/jac/dkaa516
|View full text |Cite
|
Sign up to set email alerts
|

Do high MICs predict the outcome in invasive fusariosis?

Abstract: Background Invasive fusariosis (IF) affects mostly severely immunocompromised hosts and is associated with poor outcome. Since Fusarium species exhibit high MICs for most antifungal agents, this could explain the poor prognosis. However, a clear-cut correlation between MIC and outcome has not been established. Objective To evaluate the correlation between MIC and outcome (6 week death rate) in patients with IF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 12 publications
1
20
2
Order By: Relevance
“…Among 22 patients treated with voriconazole monotherapy, the MIC 50 among patients who survived and died were 4 µg/mL and 8 µg/mL, respectively (p = 0.68). Likewise, no correlation between MIC and clinical outcome was observed among 21 patients treated with amphotericin B alone or in combination with voriconazole (29 patients) [67]. The lack of correlation between MIC and outcomes is in agreement with a study that showed similar response rates with voriconazole and amphotericin B, despite the higher MICs for voriconazole observed in antifungal susceptibility tests [23].…”
Section: Antifungal Susceptibilitysupporting
confidence: 77%
“…Among 22 patients treated with voriconazole monotherapy, the MIC 50 among patients who survived and died were 4 µg/mL and 8 µg/mL, respectively (p = 0.68). Likewise, no correlation between MIC and clinical outcome was observed among 21 patients treated with amphotericin B alone or in combination with voriconazole (29 patients) [67]. The lack of correlation between MIC and outcomes is in agreement with a study that showed similar response rates with voriconazole and amphotericin B, despite the higher MICs for voriconazole observed in antifungal susceptibility tests [23].…”
Section: Antifungal Susceptibilitysupporting
confidence: 77%
“…Voriconazole is actually the most important antifungal, which in addition to locally applied drugs, can be given intravenously. This therapy should be taken into consideration irrespective of the in vitro susceptibility, since good clinical response in hematologic patients could be observed even when administered in cases with resistant pathogens and vice versa [49]. Another option could be terbinafine, although the final clinical value of this drug in clinical cases of fungal keratitis caused by the Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, since these methods are not widely available and because species identification adds little to treatment decisions, we gave 1 point for these procedures. The same is true for antifungal susceptibility tests, since there is no correlation between MIC and the outcome 8 . There are no randomised studies evaluating different treatment regimens for the treatment of invasive fusariosis.…”
Section: Discussionmentioning
confidence: 99%
“…The same is true for antifungal susceptibility tests, since there is no correlation between MIC and the outcome. 8 There are no randomised studies evaluating different treatment regimens for the treatment of invasive fusariosis. Furthermore, although recovery of immunity is the main prognostic factors, the role of adjunctive therapies such as G-or GM-CSF and granulocyte transfusions in the treatment is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation